I···N Halogen bonding in 1:1 co-crystals formed between 1,4-diiodotetrafluorobenzene and the isomeric n-pyridinealdazines (n = 2, 3 and 4): Assessment of supramolecular association and influence upon solid-state photoluminescence properties - Yeo, Chien Ing *; Tan, Yee Seng *; Kwong, Huey Chong*; Lee, Vannajan Sanghiran; Tiekink, Edward R. T. * (Royal Society of Chemistry, 2022)
1:1 Co-crystals formed between 1,4-diiodotetrafluorobenzene and each of the three isomeric npyridinealdazines (n = 2, 3 and 4) have been characterised by X-ray crystallography, a variety of spectroscopic methods, viz. IR, Raman, NMR: solution- and solid-state (13C CP MAS and 13C HPDEC MAS) and fluorescence as well as by computational chemistry techniques. The primary connection between the respective coformers arises from I···N halogen bonds which give rise to one-dimensional supramolecular chains of varying topology depending on the position of the nitrogen atom in the n-pyridinealdazine isomer. The energies calculated for the I···N contacts are relatively small, varying from -5.4 to -6.3 kcal/mol, with the maximum being in the crystal of the 2 n = 3 isomer. Notable in the molecular packing are C-I···π(pyridine) and C–F···π(arene) interactions in the crystals with the 3- and 4-pyridinealdazine coformers, respectively. The cocrystal formed by 2-pyridinealdazine exhibited fluorescence emission.